Pengalaman Belajar Mahasiswa PGSD pada Mata Kuliah Inovasi Pendidikan Melalui Pembelajaran Kontekstual dengan Pendekatan Literasi Media Massa Online - Holy Ichda Wahyuni (Journal on Education, 2023)
Education in the 21st century requires students to have critical thinking skills and improve literacy skills. The results of the 2018 Program for International Student Assessment (PISA) show that Indonesia is still at a low level in the literacy category for reading and writing. So this study aims to describe the learning experiences of PGSD students in educational innovation courses through contextual learning with an online mass media literacy approach. This research is a qualitative research and uses a descriptive method. Data collection through documentation, observation, and questionnaires. Subjects as well as respondents in this study were PGSD students at Muhammadiyah University Surabaya semester VI who were programming educational innovation courses. the results of this study indicate that contextual learning with an online mass media literacy approach is relevant to be applied to educational innovation courses, to build meaningful student learning experiences. As many as 80% of students taking educational innovation courses have succeeded in independently publishing opinion articles in online mass media and obtaining topic ideas from ideas and arguments that have been hidden so far. 100% of students said they were happy with this experience, and were motivated to repeat the same experience.